Filming fiction Tagore, Premchand, and Ray - Asaduddin, M. (Mohammad), 1958-; Ghosh, Anuradha, 1971- (New Delhi ; Oxford : Oxford University Press, 2012)
An exploration of the mutual relationship between literature and film in an Indian context, this title discusses three iconic figures of Indian cultural life - Rabindranath Tagore Premchand, and Satyajit Ray - to present a specialised study of the complex process of mediation from printed words to images.
Selected conference papers.
Description based on print version record.
Includes bibliographical references.
Keywords: Ray, Satyajit, -- 1921-1992 -- Criticism and interpretation -- Congresses; Tagore, Rabindranath, -- 1861-1941 -- Film adaptations -- Congresses; Premacanda, -- 1881-1936 -- Film adaptations -- Congresses; Film adaptations -- India -- History and criticism -- Congresses